Spiritual literacy in John Wesley's Methodism reading, writing, and speaking to believe - Tolar Burton, Vicki 1945- (Waco, Tex. Baylor Univ. Press, 2008)
Introduction : John Wesley and the rhetorical and literacy practices of early Methodism -- John Wesley's literacy genealogy : parental patterns and practices -- Writing to believe : diaries and journals as spiritual literacy -- Speaking to believe : literacy and rhetorical practices of traveling preachers -- Walking in light, walking in darkness : Methodist women's changing rhetorical space -- The mystic and the Methodists : account of the experience of Hester Ann Rogers -- Reading to believe : John Wesley's book inventory (1791) -- Climbing boys and spinning girls : school on Sunday for laboring children -- Conclusion : the witness of their own spirits
Introduction : John Wesley and the rhetorical and literacy practices of early Methodism -- John Wesley's literacy genealogy : parental patterns and practices -- Writing to believe : diaries and journals as spiritual literacy -- Speaking to believe : literacy and rhetorical practices of traveling preachers -- Walking in light, walking in darkness : Methodist women's changing rhetorical space -- The mystic and the Methodists : account of the experience of Hester Ann Rogers -- Reading to believe : John Wesley's book inventory (1791) -- Climbing boys and spinning girls : school on Sunday for laboring children -- Conclusion : the witness of their own spirits.
Includes bibliographical references and index
Archivierung prüfen
Archivierung/Langzeitarchivierung gewährleistet
Archivierung prüfen
Keywords: Wesley, John -- 1703-1791; Wesley, John 1703-1791; Literacy -- England -- History -- 18th century; Literacy -- History -- 18th century -- England; Methodism; Spiritual Formation; England -- Church history -- 18th century; England -- Church history -- 18th century; Katalog